Mutant Prevention Concentration Siprofloksasin Terhadap Escherichia coli Patogen dari Kloaka Broiler Secara In Vitro - Maria Fatima Palupi; Eli Nugraha; Meutia Hayati; Neneng Atikah (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
Mutant prevention concentration (MPC) is an in vitro test used to determine the lowest drug concentration needed to inhibit the growth of a single-step-mutant bacterial subpopulation. The purpose of this study was to determine the MPC value of ciprofloxacin against pathogenic Escherichia coli to obtained the range of mutant selection windows (MSW) of ciprofloxacin. Ciprofloxacin is a quinolone group that is included in the Highest Priority Critically Important Antimicrobials for Human Medicine but is also used for the treatment of bacterial infections in production animals. Twenty-four of pathogenic E. coli isolates sensitive to ciprofloxacin were tested to obtain MPC values and minimum inhibitory concentration (MIC) values. Test the MPC and MIC values to get the MSW range is done by the method of agar dilution. Mueller-Hinton agar containing standard ciprofloxacin was inoculated with 1010 cfu E. coli for the MPC test and 104 for the MIC test. Based on the MPC test results, the MPC value of ciprofloxacin was 4-64 μg / mL (22.96 ± 19.07 μg / mL) and there was one isolate which had an MPC> 256 μg / mL. These results give a wide range of MSW with a lower limit of the MIC value of 0.25 - 2 µg / mL (0.55 ± 0.37 µg / mL) to the upper limit of the MPC value of 4-64 µg / mL (22.96 ± 19.07 μg / mL). Based on the results of this MPC assessment it can be concluded that the dose of ciprofloxacin in production animals has a wide range of MSW that is allow for single-step mutants.